Tribological properties of plasma nitrided inconel 718 - Aw, Poh Koon (2009)
Inconel 718 was plasma nitrided using the various controlling parameters such as treatment temperature, treatment time and N2/H2 gas composition. It was found that the case growth rate is proportional to the square root of treatment time. Maximum microhardness of 1290HK which was 3 times harder than the bulk metal was obtained with 600°C and N2/H2=1/1 after 9 hours of treatment. An uniform case depth of up to 10.5µm was obtained with 600°C and N2/H2=9/1 after 9 hours of treatment. A columnar structure caused by prolonged treatment under ionic bombardment was observed on the nitrided surface.